Burden on Family Caregivers Caring for Patients with Cancer in Indonesia - Wenny Savitri; Suwarno Suwarno (Proceedings Series on Health & Medical Sciences, 2021)
Cancer diagnosis has detrimental effects on patients’ families since they have to take care of the patients, resulting in caregivers' burden. This study aimed to investigate the burden of family caregivers caring for cancer patients. A descriptive quantitative study was applied to 60 family caregivers of cancer patients in a government hospital in Yogyakarta. Data were gathered using sociodemographic and health-related instruments and Zarit Burden Interview, then analyzed by using descriptive statistics. The results showed all family caregivers expressed their feelings of the intensity of burden (60% little or no burden, 36.7% mild-to-moderate, 3.3% moderate-to-severe), and none of them expressed severe burden. The majority were patients' children, married males, over 40 years old, and small family members living in the same house in a rural area. They went to high school or university, working in private sector, with monthly family income were below a minimum standard. They spent 1-6 hours per day for caregiving without experience in caring. They also did not have any chronic diseases, whom the majority of patients they were taking care of had third stadium of breast cancer without metastasis with chemotherapy. To conclude, most caregivers experienced little or no burden in caring for their family members with cancer.